Relive Intramuros an advertising campaign for the local tourists of Intramuros - Dedel, Samantha Nicola C. (2013)
Intramuros was the center of political, military and religious power of the Spaniards in the Philippines during the 19th century giving it an important defining role to Filipinos. Today, although the walled city is considered to be a historical treasure, knowledge of the old city no longer reached a wide audience and no longer appealed to the interest of even the locals who are geographically near. It seems that this generation is becoming more detached from the past. Today, only a few locals come to visit occasionally for a glimpse of history. Although the current tourism plan of Intramuros is able to retain its historical integrity it is not successful in catching the attention of the local audience, emphasizing Intramuros' relevance in defining the Filipino identity, promoting the importance of cultural heritage and convincing the need to come back. Added factor is the emergence of competitive locations in the vicinity. Locals will be more interested and come often at longer intervals if Intramuros competes with the modern destinations in the vicinity. This is possible if people knew what they can do and find inside the city. Knowledge if Intramuros and its importance to the Philippine national identity can be spread with the help of an adveritsing campaign for locals in Metro Manila.
"April 2013"
Thesis (BFA)--University of the Philippines Diliman.
Keywords: Advertising campaigns